INFLUENCE OF N, P AND K FERTILIZATION ON YIELD AND QUALITY OF POTATO IN EASTERN UTTAR PRADESH - Singh, M C.; Singh, R K. (Potato Journal, 2013)
Three field experiments, one each for N (0, 80, 120, 160 and 200 kg/ha), P2O5 (0, 50, 100, 150 and 200 kg/ ha) and K2O (0, 50, 100, 150 and 200 kg/ha) were carried out, with other two incorporated as standard dose (N: 120, P2O5: 60 and K2O: 80 kg/ha) at Varanasi to find out the best NPK combination for eastern Uttar Pradesh. Increasing doses of N, P and K up to 200 kg/ha improved tuber yield. However, tuber yield and related yield traits significantly improved only up to 120, 100 and 100 kg/ha of N, P2O5 and K2O, respectively. Per cent dry matter and starch content were significantly higher at lower levels of N and K.